1999
DOI: 10.1046/j.1365-2648.1999.00883.x
|View full text |Cite
|
Sign up to set email alerts
|

A journey to becoming: the student nurse in transition

Abstract: The study reported in this paper explored the nature of the transition experienced by student nurses in their journey to becoming qualified nurses. In keeping with the developing relationship between the disciplines of anthropology and nursing, the methodology of choice was ethnography. Data were collected by open-ended questionnaires and interviews with key informants from one English College of Nursing undertaking Diploma level Project 2000 Adult Branch Studies. Thematic analysis of the data revealed an ill-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(40 citation statements)
references
References 13 publications
0
38
1
1
Order By: Relevance
“…This result is consistent with those of other studies [3,13,14] that reported the clinical practice experience of nursing students as a sense of gap between theories and actual practice, confusion of the identity of nursing, chaos coming from various dynamic models. The clinical practice of nursing students is an unclear learning transition that entails role conflicts and vague boundaries [15] .…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with those of other studies [3,13,14] that reported the clinical practice experience of nursing students as a sense of gap between theories and actual practice, confusion of the identity of nursing, chaos coming from various dynamic models. The clinical practice of nursing students is an unclear learning transition that entails role conflicts and vague boundaries [15] .…”
Section: Discussionmentioning
confidence: 99%
“…There is a general consensus in the literature that a newly qualified nurse experiences significant stress (Charnley, 1999;Holland, 1999;Godinez et al, 1999;Ross and Clifford, 2002). But Hyde and Brady (2002) note that the student years are not completely stress free either.…”
Section: Role Transitionmentioning
confidence: 99%
“…All participants were from a single site in Ireland and a small sample limited generalisability, as acknowledged by the author. Holland (1999) has explored the transition experiences of the student nurse throughout training in England using an ethnographical approach. Despite theoretical evidence to support supernumerary status, there appears to be a conflict in the role of the non-waged student between that of student and that of a worker.…”
Section: Effects Of Supernumerary Status On the Student Nursementioning
confidence: 99%
“…As conflicts may develop during their transition, mentoring can facilitate negotiations and adaptation. Mentors are viewed as the catalysts to gaining the knowledge and skills required to perform the new role within the new social and/or professional group (Barton, 2007;Holland, 1999).…”
Section: Social Transition Modelmentioning
confidence: 99%